Association of Cerclage with Composite Adverse Outcomes among Women Delivered at 36 Weeks or Later - Stephens, Angela J.; Chen, Han-Yang; Chauhan, Suneet P.; Sibai, Baha (American Journal of Perinatology, 2020)
Objective This study aimed to compare the maternal and neonatal adverse outcomes among singletons delivered at 36 weeks or later with cerclage during index pregnancy versus those without cerclage.Study Design This retrospective cohort study utilized the U.S. vital statistics datasets from 2011 to 2013. Inclusion criteria were women with nonanomalous singletons, with and without cerclage placement, without diabetes or hypertensive disorders, and delivered at 36 to 41 weeks. The coprimary outcomes were composite maternal and neonatal adverse outcomes. Composite maternal adverse outcome included admission to intensive care unit, maternal transfusion, ruptured uterus, unplanned hysterectomy, or unplanned operating room procedure. Composite neonatal adverse outcome included Apgar score less than 5 at 5 minutes, assisted ventilation for more than 6 hours, neonatal seizure, birth injury, or neonatal death. Secondary outcomes were chorioamnionitis and cesarean delivery. Multivariable Poisson's regression models with error variance were used while adjusting for confounders. Adjusted relative risk (aRR) with 95% confidence intervals (CIs) were calculated.Results Of the 8,508,228 women who met inclusion criteria, 0.2% had a cerclage and reached 36 weeks. Composite maternal (aRR: 2.04; 95% CI: 1.76–2.36) and neonatal (aRR: 1.28; 95% CI: 1.11–1.47) adverse outcomes were significantly higher among those with cerclage than those without cerclage. Chorioamnionitis (aRR: 1.47; 95% CI: 1.30–1.67) and cesarean delivery (aRR: 1.10; 95% CI: 1.08–1.12) were also significantly higher in women with cerclage than those without cerclage.Conclusion There is an association between increased composite maternal and neonatal adverse outcomes among women with cerclage who delivered at 36 to 41 weeks as compared with those without cerclage.Key Points
Keywords: cerclage; maternal outcomes; neonatal outcomes; cervical insufficiency